Complete demand systems of food in Malaysia - Tey, Yeong Sheng; Shamsudin, Mad Nasir; Mohamed, Zainal Abidin; Abdullah, Amin Mahir; Radam, Alias (Czech Academy of Agricultural Sciences, 2008)
As a one of the most rapidly developing countries in Asia, there have been notable changes in Malaysian food consumption pattern. Such changes in Malaysia play an important role in the outlook for future in Malaysian agri-food industry. By using Household Expenditure Survey 2004/2005 data, this study aims to build a complete demand system of food in Malaysia via Linear Approximate Almost Ideal Demand System (LA/AIDS), with incorporation of the Stone price index and the Laspeyres price index respectively. The empirical results show that the application of the Laspeyres price index produces more plausible estimates of expenditure and own-price elasticities in Malaysia. In the estimation of the LA/AIDS with incorporation of the Laspeyres price index, the estimated expenditure elasticities show that demands for meat (1.4064), fish (1.2440), vegetables (1.1729), and fruits (1.0905) are likely to grow faster than other traditional main calorie sources-rice (0.9091) and bread & other cereals (0.3177) in corresponding to positive income effect in future. This study shows that as Malaysian society becomes more affluent, Malaysian consumers are increasingly seeking for higher value protein based products, as well as functional healthy foods.